Стан мелатонінутворювальної функції епіфіза в людей похилого віку з порушенням вуглеводного обміну - Korkushko, O.V.; Shatilo, V.B.; Antoniuk-Shcheglova, I.A.; Bondarenko, O.V.; Ishchuk, V.O. (Ендокринологія | Endokrynologia, 2012)
Стан мелатонінутворювальної функції епіфіза в людей похилого віку з порушенням вуглеводного обміну